Evaluating the efficiency and total factor productivity improvement of Agribank district-level branches in Dak Lak province - Vương Hồng, Lĩnh; Hong Minh, Tuấn; Niêm, Lê Đức (Tay Nguyen Journal of Sciences, 2025)
The main objective of this study is to develop a performance model that assesses the relative efficiency and the potential for total factor productivity improvement of bank branches. By comparing this model to the traditional evaluation method used by Agribank Dak Lak, the study aims to identify strengths and weaknesses and draw managerial implications from the comparison. Valuable insights into branch performance are obtained through the assessment of efficiency scores. The findings indicate that with improved management and utilization of given inputs, all branches can enhance their performance by 24% in 2020, 35.2% in 2021, and 29.4% in 2022 without input modifications. However, it is noteworthy that due to the impact of the COVID-19 pandemic and unfavorable conditions, most branches could not increase their total productivity between 2020 and 2022. Only two branches, namely the Tay Nguyen University Branch and the Buon Don Branch, improved their Total Factor Productivity (TFP) from 2021 to 2022. Considering these findings, several managerial implications can be derived for Agribank Dak Lak.